Analysis of Violations of Grice's Principles of Cooperation in the Mata Najwa Adu Kuat Program on Constitutional Affairs - Mauliyati Sari, Dewi; Suwadi, Suwadi; Rokhmawan, Tristan (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2024)
This research aims to analyze violations of Grice's principles of cooperation in the Mata Najwa program